Effectiveness of the Expanded Maternal and Neonatal Survival Program in the Reduction of Maternal Mortality in Tegal, Central Java - Karina Cibro, Adeyle Datna; Demartoto, Argyo; Sulaeman, Endang Sutisna (Journal of Maternal and Child Health, 2016)
Background: Maternal mortality rate is one of the sensitive indicators of population health in a country. Various measures have been implemented to reduce maternal mortality rate, including the Expanding Maternal And Neonatal Survival (EMAS) program. This study aimed to evaluate the effectiveness of the Expanded Maternal and Neonatal Survival program in the reduction of maternal mortality in Tegal, Central Java.Subjects and Method: This was a qualitative evaluative study using context, input, process, product (CIPP) framework. This study was conducted in Tegal, Central Java. The data were collected by in-depth interview, observation, and document review. The primary key informants of this study consisted of 10 subjects, including EMAS team, Head of the District Health Office Tegal, Head of Pagerbarang Health Center, Head of Dukuhwaru Health Center, their coordinating midwife, and community as the program beneficiary.Results: EMAS program was implemented in Tegal because of high maternal mortality rate and lack of community awareness on the importance of visiting health care facility. During the program implementation the district government synergized various stakeholders to realize good governance. Stakeholders work together according to each other task and function. EMAS program has resulted in improved skill of the doctors, midwives, and nurses in tackling emergency cases, so that the emergency cases can be tackled faster, and community awareness use health facilities. The barrier factor was the insufficient number of mentoring health personel.Conclusion: The EMAS program in Tegal district, which aims to reduce maternal mortality rate has been implemented effectively. The emergency referral system is well implemented. Working groups had performed tasks and functions well with adequate responsibility.Keywords: evaluation, EMAS program, maternal mortality rateCorrespondence:ÃÂ Adeyle Datna Karina Cibro. Masters Program in Public Health, Sebelas Maret University, Surakarta. Mobile: 085642596407.Journal of Maternal and Child Health (2016), 1(4): 250-256https://doi.org/10.26911/thejmch.2016.01.04.06